Korelasi Vitamin D terhadap Kadar Antimullerian Hormone pada Pasien Sindroma Ovarium Polikistik dengan Obesitas di Kota Palembang - Usman, Fatimah; Putra, Hadrians Kesuma; Abadi, A; Siahaan, Salmon Charles (Fakultas Kedokteran Universitas Riau, 2024)
Polycystic Ovary Syndrome (PCOS) is one of the most common endocrine system disorders affecting women of reproductive age. One of the biomarkers for the diagnosis of PCOS is Anti Mullerian Hormone (AMH). Meanwhile, women with PCOS are at higher risk for vitamin D deficiency. The research aims to examine vitamin D and AMH for PCOS women with obesity. PCOS or also known as hyperandrogenic anovulation (HA), or Stein-Leventhal syndrome, is one of the most common endocrine system disorders affecting women of reproductive age. This study was analytic with a cross-sectional approach. The subjects were women with PCOS who went to Dr. M. Hoesin Sriwijaya University (n=30). Inclusion criteria were patients diagnosed with PCOS using Rotterdam, patients who had not received therapy for insulin resistance, and were obese. The exclusion criteria were that the patient couldn’t fulfill Rotterdam criteria and/or option not to participate in this study. The results were that most patients experienced oligomenorrhea (76.7%), the age mean was 31.17 years, and the BMI mean was 33.4 kg/m2. The Spearman correlation test showed a negative correlation between AMH and Vitamin D (p=0.011, correlation coefficient=-0.458). There was no correlation between BMI and vitamin D in PCOS patients, but there was a negative correlation between AMH and vitamin D levels.